Microbial Cell Factories - Wegrzyn, Grzegorz
Microbial Cell Factories is an open access, peer-reviewed, online journal that covers any topic related to the development, use and investigation of microbial cells as producers of recombinant proteins and natural products, or as catalyzers of biological transformations of industrial interest. Microbial Cell Factories is the world leading, primary research journal fully focusing on Applied Microbiology.